No evidence of improvement in neuropathy after renal transplantation in patients with end stage kidney disease. Issue 3 (10th June 2021) - Ferdousi, Maryam; Azmi, Shazli; Kalteniece, Alise; Khan, Saif Ullah; Petropoulos, Ioannis N.; Ponirakis, Georgios; Alam, Uazman; Asghar, Omar; Marshall, Andrew; Soran, Handrean; Boulton, Andrew J. M.; Augustine, Titus; et al.
Abstract: To assess the impact of renal transplantation on peripheral nerve damage in patients with chronic kidney disease (CKD). Fifteen patients with CKD (eGFR <15 mL/min/1.73 m 2 ) underwent longitudinal assessment after renal transplantation (age: 56.88 ± 2.53 years, eGFR: 46.82 ± 4.86) and were compared with 15 age‐matched controls (age: 58.25 ± 2.18 years, eGFR: 86.0 ± 2.0). The neuropathy symptom profile (NSP), neuropathy disability score (NDS), vibration perception threshold (VPT), cold and warm sensation threshold (CST and WST), cold and heat induced pain (CIP and HIP), deep breathing heart rate variability (DB‐HRV), nerve conduction studies and corneal confocal microscopy (CCM) to quantify small nerve fibre pathology, were undertaken within 1‐month of renal transplantation (baseline) and at 6, 12 and 24 months of follow up. There was no significant difference in NSP ( P  = .1), NDS ( P  = .3), VPT ( P  = .6), CST ( P  = .2), CIP ( P  = .08), HIP ( P  = .1), DB‐HRV ( P  = .9) and sural ( P  = .4) and peroneal ( P  = .1) nerve amplitude between patients with CKD and controls at baseline. However, sural ( P  = .04), peroneal ( P  = .002) and tibial ( P  = .007) nerve conduction velocity and tibial nerve amplitude ( P  = .03) were significantly lower, WST ( P  = .02) was significantly higher and corneal nerve fibre density ( P  = .004) was significantly lower in patients with CKD compared with controls. There was no significant change in NSP, NDS, quantitative sensory testing, DB‐HRV, nerve conduction or CCM parameters 24 months after renal transplantation. There is evidence of small and large fibre neuropathy in patients with CKD, but no change up to 24 months after successful renal transplantation.